LEGAL RESPONSIBILITY FOR THE ROLE OF ONLINE TRANSPORTATION COURIER SERVICES IN DRUG TRAFFICKING - Siahaan, Ricardho; Sinaulan, Ramlani Lina; Ismed, Mohamad (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
In this modern period, drug trafficking in Indonesia has adopted a new mode of operation, with drug traffickers utilizing online transportation courier services to facilitate drug delivery to their destination, in an effort to avoid and/or reduce the risk of legal proceedings. The purpose of this research is to analyze and determine the existence of law enforcement problems in handling the role of online transportation courier services that help drug trafficking. This research uses Normative Juridical methodology. The data used for the formulation of the problem is secondary data consisting of primary, secondary and tertiary legal documents. The results of the analysis show that with regard to law enforcement and accountability, each construction of the Intermediary Articles contained in Law Number 35 of 2009 concerning Narcotics relating to acts committed by couriers does not all fulfill the offense elements of each article. Based on Article 132 when couriers are unable to prove good faith as an online driver, such as not having the authority to inspect goods to be sent, courier service companies do not or have not supported goods scanning facilities, so they can enter into a conspiracy offense. However, even though the actions carried out by online couriers have fulfilled the formulation offense, they are not necessarily accountable. For the sake of creating a sense of justice for society, it is necessary to add new norms to the provisions of Article 114 paragraph (1) of the Narcotics Law and Article 114 paragraph (2) of the Narcotics Law.